2020
DOI: 10.3389/fcell.2020.613416
|View full text |Cite
|
Sign up to set email alerts
|

Control of T-Cell Activation and Signaling by Amino-Acid Catabolizing Enzymes

Abstract: Amino acids are essential for protein synthesis, epigenetic modification through the methylation of histones, and the maintenance of a controlled balance of oxidoreduction via the production of glutathione and are precursors of certain neurotransmitters. T lymphocytes are particularly sensitive to fluctuations in amino acid levels. During evolution, the production of amino-acid catabolizing enzymes by mainly antigen-presenting cells has become a physiological mechanism to control T-cell activation and polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 114 publications
(124 reference statements)
1
10
0
Order By: Relevance
“…4). 18 It was reported that HIV+ patients have a higher ratio of phenylalanine/tyrosine than healthy individuals, 19 and our results are in agreement which can be verified from the metabolite box plot in Fig. 2.…”
Section: Hiv Before Glutamine Administration (Bt) Versus the Same Pat...supporting
confidence: 90%
“…4). 18 It was reported that HIV+ patients have a higher ratio of phenylalanine/tyrosine than healthy individuals, 19 and our results are in agreement which can be verified from the metabolite box plot in Fig. 2.…”
Section: Hiv Before Glutamine Administration (Bt) Versus the Same Pat...supporting
confidence: 90%
“…T cells are exquisitely sensitive to the deprivation of L-arginine, resulting in proliferative arrest (51) and, in the case of CD4 + cells, the promotion of Th2 and T reg phenotypes (52). Our scGEX data revealed that in our model of NB, Arg1 expression was restricted to monocytic cells, with minimal amounts detected within the tumor cells (Fig.…”
Section: Bone Marrow-derived Ccr2 + Myeloid Cells Drive Neuroblastomamentioning
confidence: 66%
“…11 Glioblastoma is particular in that it is suspected to be derived from neural stem cells 15 and isoform 2 of IL4I1 is expressed in several neural cell types, 16 with a still undefined function that may involve control of the level of neurotransmitter amines. 17,18 In the same work, they demonstrate for the first time that IL4I1 promotes glioblastoma motility in vitro, an effect that may be highly relevant for metastatic processes. Finally, their work brings new insights by proposing that the immunosuppressive effect of IL4I1 in tumors is mediated by activation of the ligand-activated transcription factor aryl hydrocarbon receptor (AHR).…”
Section: Introductionmentioning
confidence: 83%